Предмет: Математика,
автор: Аноним
3)5(x-1)+2(x+3)-7x=
X - 1-2(x+2)-1=
(2a+1)*2-a+5=
4)2(a+3)-(a-3)+1=
3(a+b-1)-3a-3b+3=
5(1-2a)-3(a+1)=
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
Приложения:
![](https://files.topotvet.com/i/8ea/8ea6229824dbf0b981acb3f3df6062de.jpg)
Похожие вопросы
Предмет: Українська мова,
автор: валя567843433
Предмет: Русский язык,
автор: Пахомвернись
Предмет: Английский язык,
автор: Аришкамишк
Предмет: Химия,
автор: egenia2017
Предмет: Математика,
автор: panini1234567